THE IMPACT OF SOCIAL MEDIA ON CHANGES IN SOCIAL INTERACTION PATTERNS IN CITIES - Aqila, Azzahra Nayla; Muti’ah, Eva (Bina Bangsa International Journal of Business and Management, 2025)
Objective This is to provide a symbol of solidarity, self-existence, and even a tool to build a personal image in cyberspace. This shows that social media is not just a communication tool, but has emerged as a platform for the formation of digital culture that is thick with nuances of novelty, flexibility and expressiveness. Method What is being used is the literature approach method which contains facts that are being discussed and selected because they can provide a detailed explanation of this problem, by analyzing 50 international and national journals that have been published online. Based on results analysis of literacy can be concluded that the use of social media has a big impact on the user's social lifestyle. According to Chenet al (2016), the use of social media increases collaborative learning among students. The good effects of social media are that it makes it easier to interact with other people, gain relationships, allows easy and free communication and expression, expands the latest information, and saves costs in obtaining information. Recommendation a combination of more adaptive regulations, increased supervisory capacity, close collaboration between government, social media platforms and society is needed. A social media strategy in building national integration in the digital era requires a comprehensive approach to exploit the potential of digital platforms as a unifying tool. This strategy is to increase digital literacy, by teaching people how to verify information through trusted sources such as fact-checking sites, and also by creating videos, infographics or simple animations about the importance of unity and diversity. One additional approach is to form online communities.